2016
DOI: 10.1016/j.ajhg.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Phenomics Analysis Deconvolutes Genes Mutated in Intellectual Disability into Biologically Coherent Modules

Abstract: Intellectual disability (ID) disorders are genetically and phenotypically extremely heterogeneous. Can this complexity be depicted in a comprehensive way as a means of facilitating the understanding of ID disorders and their underlying biology? We provide a curated database of 746 currently known genes, mutations in which cause ID (ID-associated genes [ID-AGs]), classified according to ID manifestation and associated clinical features. Using this integrated resource, we show that ID-AGs are substantially enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
239
0
13

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 268 publications
(267 citation statements)
references
References 56 publications
5
239
0
13
Order By: Relevance
“…The advances in Intellectual Disability gene discovery have identified many causative genes, but about half of cases do not have a known etiology (Ellison et al 2013). Currently, more than 700 genes are reportedly involved in a wide variety of ID-associated phenotypes with multiple clinical presentations (Kochinke et al 2016), and around 2000 genes are estimated to be implicated with ID in total (van Bokhoven 2011). Confirming pathogenicity of gene mutations is a challenge, given the extensive genetic heterogeneity of ID.…”
Section: Introductionmentioning
confidence: 99%
“…The advances in Intellectual Disability gene discovery have identified many causative genes, but about half of cases do not have a known etiology (Ellison et al 2013). Currently, more than 700 genes are reportedly involved in a wide variety of ID-associated phenotypes with multiple clinical presentations (Kochinke et al 2016), and around 2000 genes are estimated to be implicated with ID in total (van Bokhoven 2011). Confirming pathogenicity of gene mutations is a challenge, given the extensive genetic heterogeneity of ID.…”
Section: Introductionmentioning
confidence: 99%
“…Variants were filtered for known and candidate ID genes using a published database. 1 For patient 2, we used the 'Kingsmore panel'. About 1222 genes were enriched (Illumina TruSeq Custom Enrichment Kit) and sequenced (Illumina MiSeq 2 × 100 bp paired-end), and 526 known ID-associated genes 13 of the 1222 genes were specifically analyzed.…”
Section: Exome Sequencing Data Analysismentioning
confidence: 99%
“…The study was approved by the ethical committee of the canton of Zurich. Filtering for rare, non‐synonymous exonic, and splice site variants in 821 known and 424 candidate ID genes (based on the SysID database, [Kochinke et al, 2016]), considering both dominant and recessive modes of inheritance, revealed pathogenic de novo loss of function mutations in ARID1B in P2 and P3. In P2, we identified a heterozygous deletion of 4 bp (NM_020732.3:c.5570_5573del) in the last coding exon of ARID1B , which causes a frameshift resulting in a premature truncation after 16 amino acids and thereafter a significantly truncated protein (p.Lys1857Serfs*17).…”
Section: Tablementioning
confidence: 99%